Distance education students' mental health, connectedness and academic performance during COVID-19: A mixed-methods study. Issue 1 (2nd January 2022) - Di Malta, Gina; Bond, Julian; Conroy, Dominic; Smith, Katy; Moller, Naomi
Abstract: In this study, we investigated the links between distance education students' mental health, connectedness, and academic performance during COVID-19, using a mixed-methods sequential explanatory design. Online survey responses with a sample of 208 distance education students—aged 18–84, 144 females, 60 males, three nonbinary individuals, most (163) self-identified as White British—were analyzed using multiple regression, mediation, and content analysis. Connectedness (loneliness and a sense of connection to university) mediated links between mental health (wellbeing and anxiety) and academic performance. A subsample analysis with students who met clinical concern thresholds of anxiety and wellbeing ( n = 123) revealed that poorer wellbeing was associated with less emotional intimacy, more loneliness, and poorer self-reported academic performance. Anxiety was associated with less emotional intimacy and higher relational intensity with one person, and poorer self-reported academic performance. These pathways were triangulated and contextualized within students' experiences of connectedness. Future research using a longitudinal design is needed to establish causal links.